Public Discourse of the Chilean Ministry of Education on School Violence and Convivencia Escolar: A Subjective Theories Approach. - Castro-Carrasco, Pablo; Gubbins, Verónica; Caamaño, Vladimir; González-Palta, Ingrid; Rodríguez-Pastene Vicencio, Fabiana; Zelaya, Martina; Carrasco-Aguilar, Claudia (MDPI, 2025)
This study analyzed subjective theories on school violence and convivencia escolar expressed in the public discourse of the Chilean Ministry of Education in 2022. This research focused on the return to in-person learning, a time when concerns about violence in schools increased and public policies aimed at addressing it were launched. Inductive content analysis and grounded theory techniques were used to examine 66 tweets issued by official ministry accounts during 2022. The analysis identified three interpretative sets. The first suggests that although violence has external structural causes, it must be eradicated from schools. The second links convivencia escolar with well-being and socioemotional skills, but without an explicit association with violence. The third locates the origin of psychological distress in external factors but assigns its management to the school system. A predominance of expert knowledge existed in the promoted solutions. These findings are discussed based on the idea that the Ministry of Education’s discourse on Twitter not only informs but also seeks to shape educational common sense and validate public policies. This raises questions about its impact on the interpretive autonomy of school communities.
Keywords: Política educativa; Violencia en la escuela; Subjective theories; School violence; Convivencia escolar; Public discourse; Educational policy